Arbitrage et conciliation aux premiers siècles de l’Islam : théories, pratiques et usages sociaux - Mathieu Tillier (Revue des Mondes Musulmans et de la Méditerranée)
Arbitration (taḥkīm) and settlement by mutual agreement achieved through conciliation (ṣulḥ) appear at first glance as forms of justice parallel to state courts. Based on narrative and legal sources, this article explores the articulations of such systems with official institutions and identifies their main judicial and social uses in the Eastern provinces of the caliphate during the first four centuries of Islam. It appears that early on, arbitration was integrated into the general system of conflict resolution, in the form of a lower court, whose binding sentence could be appealed to state courts. Qadis also served as mediators for amicable settlements. Although the legal theory tended to minimize that role, ṣulḥ was part of current strategies enabling litigants to reduce their losses while increasing their symbolic capital.